Стратегии переработки информации при распознавании эмоций - Дмитрий Владимирович Люсин (Психология. Журнал Высшей школы экономики, 2011)
The analysis of top-down and bottom-up processes of information processing during emotion recognition was carried out. The empirical part of the work is devoted to summarizing the results of three studies which focused on the strategies of information processing used during emotion recognition. Two types of such strategies are stably distinguished. They are relevant to rational and intuitive modes of social cognition. The correlations of the strategies with the other individual characteristics are revealed.